A comparative study between the Higher Education Council system of 1993 and the universities system of 2019 in the Kingdom of Saudi Arabia - Albeshir, Saud Ghassan (Journal of Educational and Psychological Sciences, 2023)
The current research compares the articles of the Higher Education and Universities Council system issued in 1993 and the new universities system issued in 2019. The significance of the current study is due to the lack of scientific studies on lawmaking related to education in Saudi Arabia in general, as there are only a few researchers who have studied educational regulations in depth, as well as the lack of comparative studies comparing the two systems of 1993 and the system of 2019. The study aimed to identify the similarities and dissimilarities between the subjects of the 1993 system, which consists of 60 regular subjects, and the new university system, consisting of 58 regular subjects, that regulates work within public universities in the country.The study found similarities in several articles between the old and the new system, especially regarding governmental powers within universities. The researcher also discovered dissimilarities between the articles of the two systems. The most essential of these differences in the articles are those related to the articles on decision-making and administrative organization in public universities. The study uncovered some new legal articles in the 2019 system that were not mentioned in the articles of the 1993 system. Among the articles in the 2019 system are obtaining institutional and program credits, as well as the right of Saudi universities to open branches outside the country.